An Unusual and Complicated Course of a Giant Cell Tumor of the Capitate Bone - Ingo Schmidt (Case Reports in Orthopedics)
A 51-year-old female patient presented with a carpal giant cell tumor (GCT) of the right capitate bone. The lesion was initially misdiagnosed as having an osteomyelitis. First, the diagnosis of a benign GCT was confirmed by histological examination. Second, an intralesional curettage and packing of the cavity with cancellous iliac crest bone grafts combined with a fusion of the third carpometacarpal (CMC III) joint were carried out. Third, due to a secondary midcarpal osteoarthritis and a secondary scaphoid nonunion, the CMC III joint fusion plate was removed and the midcarpal joint completely excised. Fourth, in the absence of recurrence of GCT, a four-corner fusion (4CF) with a corticocancellous iliac crest bone graft and complete excision of the scaphoid bone had to be performed. Fifth, a total wrist arthroplasty (TWA) was performed due to hardware failure of 4CF with migration of a headless compression screw into radiocarpal joint which led to erosion of articular surface of the distal radius. At the 3-year follow-up that includes a 1-year follow-up after TWA, there was no recurrence of GCT, and the TWA was not failed. The patient reported that she would have the motion-preserving TWA again.